ChemInform Abstract: Catalytic Asymmetric Synthesis of 8‐Oxabicyclooctanes by Intermolecular [5 + 2] Pyrylium Cycloadditions. Issue 48 (2nd December 2014) - Witten, Michael R.; Jacobsen, Eric N.
Abstract Additionally several stereoselective complexity‐generating transformations of the 8‐oxabicyclooctane products are presented.